Distance determination in spin-correlated radical pairs in photosynthetic reaction centres by electron spin echo envelope modulation - Fursman, C; Hore, P (1999)
Distances between radicals in photosynthetic reaction centres can be determined from the strong 'out-of-phase' electron spin echo envelope modulation (ESEEM) caused by the electron spin-spin dipolar interaction. The precision with which the dipolar coupling can be measured in such experiments and the optimum strategy for sampling the time-domain spin echo signal are explored using the method of Cramér-Rao lower bounds. Consideration of the contributions to the ESEEM from anisotropic hyperfine interactions suggests that the precision is much higher than hitherto estimated and that the accuracy may not be affected if nuclear modulations are ignored.